2015
DOI: 10.1111/jth.12865
|View full text |Cite
|
Sign up to set email alerts
|

Antiphospholipid syndrome: antibodies to Domain 1 of β2‐glycoprotein 1 correctly classify patients at risk

Abstract: Summary. Background: Determination of lupus anticoagulant (LA), anticardiolipin (aCL) and b2-Glycoprotein 1 (ab2GP1) antibodies is mandatory to classify patients with antiphospholipid syndrome (APS) into risk categories. Objectives: To measure relevant antibodies, considered to be those of the IgG isotype directed towards b2GP1 and particularly those directed to Domain 1 (Dm1) of the molecule. Patients/methods: In this cross-sectional study we measured IgG ab2GP1-Dm1 by a chemiluminescent immunoassay in a grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 21 publications
6
97
2
2
Order By: Relevance
“…[25][26][27][28][29][30][31] Subsequent studies documented that anti-DI autoantibodies, being much less frequent in control populations in which antibodies against the whole molecule can be detected, provide good specificity for APS or systemic autoimmune conditions. 32,33 The opposite seems to be true for IgG antibodies against DIV-V, which are more frequent in asymptomatic aPL carriers, in patients with leprosy, in children suffering from atopic dermatitis or born from mothers affected by systemic autoimmune disorders.…”
Section: Epitope Specificity Of Anti-b2gpi Antibodies: the New Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27][28][29][30][31] Subsequent studies documented that anti-DI autoantibodies, being much less frequent in control populations in which antibodies against the whole molecule can be detected, provide good specificity for APS or systemic autoimmune conditions. 32,33 The opposite seems to be true for IgG antibodies against DIV-V, which are more frequent in asymptomatic aPL carriers, in patients with leprosy, in children suffering from atopic dermatitis or born from mothers affected by systemic autoimmune disorders.…”
Section: Epitope Specificity Of Anti-b2gpi Antibodies: the New Aspectmentioning
confidence: 99%
“…32,33 Anti-DI antibodies have been associated with both arterial and venous thrombosis with a significant increase in the odds ratio for these events. [25][26][27][30][31][32] However, the fact that the antibodies are usually detectable in patients double or triple positive for the APS laboratory classification tests and their strong association with LA positivity raise the issue whether the predictive power is dependent on this antibody subpopulation itself or simply on their presence in patients with high risk aPL profiles. Anti-DI antibodies have also been described in obstetric APS patients (even in pure obstetric patients without vascular events), although with lower prevalence and in some reports with lower titres.…”
Section: Epitope Specificity Of Anti-b2gpi Antibodies: the New Aspectmentioning
confidence: 99%
“…Several studies with the CIA aD1 assay confirmed high odds ratios for thrombosis and the role of aD1 in risk stratification [41][42][43][44]. Correlating to the higher risk, aD1 IgG are mainly present in triple-positive patients, also showing higher levels [42,43]. A limited number of studies have evaluated whether the aD1 are independent risk factors for thrombosis, and showed that aD1 had no added value to the current aPL panel [42,45].…”
Section: Other Antiphospholipid Antibodiesmentioning
confidence: 99%
“…19,20,23 Additional test reinforcing the diagnosis of definite APS include anti-domain I antibodies (detected by a chemiluminescent assay). 25 Positivity on 2 or more occasions, at least 12 weeks apart 2 may not be necessary, as positivity is seldom transient in triple--positive patients. 26 No firm association is present between the IgM isotype and thrombotic APS with a predominant or only the IgM isotype.…”
Section: 23mentioning
confidence: 99%
“…23,24 Moreover, at variance with single positivity, recent data have shown that high--risk subjects with triple-positive aPL profiles are identified early at the time of the initial screening tests without the need for confirmation after 12 weeks. 25 In light of these more recent contributions to the field, new updated criteria for the laboratory component of the diagnosis of APS should be developed.…”
mentioning
confidence: 99%